INTERNATIONAL AVIATION/AIRSPACE LAW AN OVERVIEW - Yaya Kareng (UNISSULA, 2020)
Aviation law is the branch of law that concerns flight, air travel, and associated legal and business concerns. Some of its area of concern overlaps that of admiralty law and, in many cases, aviation law is considered a matter of international law due to the nature of air travel. However, the business aspects of airlines and their regulation also fall under aviation law. In the international realm, the International Civil Aviation Organization (ICAO) provides general rules and mediates international concerns to an extent regarding aviation law. The ICAO is a specialized agency of the United Nations. In the United States and in most European nations, aviation law is considered a federal or state-level concern and is regulated at that level. In the U.S., states cannot govern aviation matters in most cases directly but look to Federal laws and case law for this function instead. For example, a court recently struck down New York's Passenger Bill of Rights law because regulation of aviation is traditionally a federal concern. Aviation law, however, is not in the United States held under the same Federal mandate of jurisdiction as admiralty law; that is, while the United States Constitution provides for the administration of admiralty,[1] it does not provide such for aviation law. States and municipalities do have some indirect regulation over aviation. For example, zoning laws can require an airport to be located away from residential areas, and airport usage can be restricted to certain times of day. State product-liabilitys law are not preempted by Federal law and in most cases, aviation manufacturers may be held strictly liable for defects in aviation products. Space law, which governs matters in outer space beyond the Earth's atmosphere, is a rather new area of law but one that already has its own journals and academic support. Much of space law is connected to aviation law.